Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1749-6632.2009.03900.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Free Dietary Glutamate on Gastric Secretion in Dogs

Abstract: The amino acid, L-glutamate, which is abundant in many foodstuffs, is a potent stimulator of gastric vagal afferents. The aim of the study was to evaluate a role of dietary glutamate in neuroendocrine control of gastric secretion of acid, pepsinogen, and fluid. In mongrel dogs with small gastric pouches surgically prepared according to Pavlov (vagally innervated) or Heidenhain (vagally decentralized), secretion in a pouch was induced by infusion into the main stomach of an amino acid-rich diet lacking glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…Glu absorption is mainly mediated by EAAT3 in the nervous system [16], gastrointestinal tract [5, 17] and skeletal muscle [18]. Our previous studies revealed that EAAT3 is a marker of intestinal growth during embryonic development in chicks [7, 19] and pigeons [2022].…”
Section: Discussionmentioning
confidence: 99%
“…Glu absorption is mainly mediated by EAAT3 in the nervous system [16], gastrointestinal tract [5, 17] and skeletal muscle [18]. Our previous studies revealed that EAAT3 is a marker of intestinal growth during embryonic development in chicks [7, 19] and pigeons [2022].…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we examined the eŠect of free glutamate on gastric acid secretion when injected directly into the main stomach of Pavlov pouch dogs. 40,41) We used an enteral liquid diet (Elental TM ) as a nutrient, which is mainly composed of a mixture of amino acids,ˆnal nutrients digested from protein.…”
Section: Physiological Significance Of Gluta-mate-induced Visceral Inmentioning
confidence: 99%
“…In support of this idea, adding MSG to an amino acid-rich diet (but not a glutamate diet) dosedependently potentiates secretion of acid, fluid and pepsinogen from vagally innervated ("Pavlov") small gastric pouches when nutrients are infused into the main stomach (isolated from the Pavlov pouch) of conscious dogs (63). These MSG effects are markedly reduced after intravenous injection of granisetron, an antagonist of 5-HT 3 R. Vagal decentralization ("Heidenhain" pouch) partly reduced the potentiating effects of dietary MSG.…”
Section: Secretion Of Digestive Juicesmentioning
confidence: 95%